Association of hepatitis B surface antigen carriage with severe malaria in Gambian children. - Thursz, MR; Kwiatkowski, D; Torok, M; Allsopp, C; Greenwood, B; Whittle, H; Thomas, H; Hill, A (1995)
Severe malaria is a major cause of childhood mortality in sub-Saharan Africa but the factors predisposing children to severe forms of malaria have not been fully elucidated. In a case-control study of over 1,200 Gambian children hepatitis B virus carriage was significantly increased amongst cases of severe malaria compared to matched controls. We suggest that this association may relate to impaired clearance of liver stage parasites in the presence of the reduced level of HLA class I antigen expression on hepatocytes infected by hepatitis B virus. If this association is causal and viral carriage predisposes to severe malaria, widespread vaccination against hepatitis B virus may reduce mortality from severe malaria.